POTENCY OF OCIMUM SANCTUM EXTRACT L OINTMENT ON THE MANAGEMENT PARTIAL-THICKNESS PALPEBRAL LACERATION, IS IT A NOVELTY TO BE CONSIDERED AS AN ALTERNATIVE THERAPY?: REVIEW ON HISTOPATHOLOGICAL CHANGES IN EXPERIMENTAL MODEL: Oral Presentation - Experimental Study - Resident - Muhammad Insanul Kamil Rery, (Ophthalmologica Indonesiana, 2024)
AbstractIntroduction & Objectives : Ocimum sanctum extract (OSE) has been shown to have antioxidant, anti-inflammatory, and antibacterial properties which are responsible for wound healing. This study aims to analyze the effect of 5%, 10%, and 15% OSE ointment on changes in collagen density and fibroblast count in Wistar rats with partial-thickness palpebral laceration.Methods : Laboratory experimental study with randomized post-test only control group design. The subjects were 30 rats divided into 5 groups: The placebo; Gentamicin 0.3%; OSE 5%; OSE 10% and OSE 15% group. The intervention was administered 2 times/day for 4 days. On the fifth day, the eyelid tissue was obtained to make histopathological preparations and to observe the collagen density and fibroblast count. Data were analyzed using Mann-Whitney, One-Way ANOVA, Kruskal Wallis, and Tamhane test. A p-value